2018
DOI: 10.1002/jcb.27920
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA XIST participates in bladder cancer by downregulating p53 via binding to TET1

Abstract: Long noncoding RNAs (lncRNAs) have been reported to take part in intracellular RNA regulatory networks and play important roles in a lot of pathological processes. Currently, lncRNA X‐inactive specific transcript (XIST) has been proved to regulate cell migration, proliferation, and apoptosis in a series of cancers. In this study, we explored whether XIST can affect cell proliferation, migration, and apoptosis in bladder cancer. The influences of XIST on the cell proliferation, cell cycle, and apoptosis were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 32 publications
(80 reference statements)
2
20
0
Order By: Relevance
“…Compared with hepatocellular carcinoma, our results indicated that increased TET1 expression induced apoptosis and inhibited the growth of U2OS cells, consistent with previous data obtained from colon cancer cells [27]. TET1 expression was recently reported to be associated with apoptosis in bladder cancer cells [28]. As shown in the present study, TET1 overexpression induced apoptosis in HU-treated cells.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with hepatocellular carcinoma, our results indicated that increased TET1 expression induced apoptosis and inhibited the growth of U2OS cells, consistent with previous data obtained from colon cancer cells [27]. TET1 expression was recently reported to be associated with apoptosis in bladder cancer cells [28]. As shown in the present study, TET1 overexpression induced apoptosis in HU-treated cells.…”
Section: Discussionsupporting
confidence: 93%
“…MAGI2-AS3 (ENST00000452320) was observed in hepatocellular carcinoma ( 52 ). Notably, it has been reported that lncRNA XIST ( 53 ), MEG3 ( 54 ), MAGI2-AS3 ( 55 ), FENDRR and ADAMTS9-AS2 ( 56 ) act as prognosis markers of patients with BC or exert significant roles in BC progression through different cancer-associated pathways. For instance, Kouhsar et al ( 56 ) revealed that based on the analysis of the ceRNA networks in the early stage of BC, the lncRNAs FENDRR, ADAMTS9-AS2 and CARMN may regulate MEG3 in NMIBC via harboring some critical miRNAs such as miR-143-3p, miR-34a-3p and miR-106a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, XIST has been shown to be associated with proliferation, apoptosis, tumor development, metastasis, patient prognosis, and response to chemo-and radio-therapies of cancer. In bladder cancer cells in vitro, targeting XIST suppressed cell invasion and proliferation by downregulation of p53 [30]. In nasopharyngeal carcinoma (NPC), targeting XIST inhibited NPC cell proliferation and invasion in vitro and NPC tumor growth in vivo [31].…”
Section: Discussionmentioning
confidence: 99%